The Effect of Transformational Leadership and Work Motivation on Teacher Performance in Junior High Schools Sungai Lilin District - Cance Melsing; Syarwani Ahmad; Sri Wahyu Indrawati (Graduate Program Magister Manajemen Pendidikan, 2026)
This research was conducted uTo find out whether there is an influence of transformational leadership and work motivation on teacher performance. The research method used is descriptive quantitative through a survey. Data were collected by distributing a “Likert Scale” Questionnaire to 82 teachers at SMP Negeri 1 Sungai Lilin, SMP Negeri 5 Sungai Lilin, SMPS Islam Ar – Riyadl and SMP Al Azhar As-Syarif. The research findings show that 1) Transformational leadership is able to influence teacher performance positively and significantly, as indicated by tcount > ttable (4.292 > 1.668) and Sig. < α (0.000 < 0.05). 2) Work motivation is able to influence teacher performance positively and significantly, as indicated by tcount > ttable (4.883 > 1.668) and Sig. < α (0.000 < 0.05). 3) Transformational leadership and work motivation together are able to influence teacher performance positively and significantly, as shown by Fcount > Ftable (19.528 > 3.11) and Sig. < α (0.000 < 0.05). With these results it can be concluded that transformational leadership and work motivation greatly influence teacher performance. This shows that the creation of a conducive work environment, increases professional commitment, and encourages teachers to carry out educational tasks effectively and with quality in teaching so that student achievement, character and positive attitudes of students increase. It is hoped that school principals can understand and apply transformational leadership consistently and sustainably, so that they can continue to motivate teachers in achieving common goals.